OVERVIEW OF THE MAINTENANCE AND MAINTENANCE MANAGEMENT SYSTEM AT THE SUNAN HOTEL SOLO - Prastowo, Ichwan (ASTONJADRO, 2020)
The purpose of this study is to find out how the building repair and maintenance management system of the building on the hotel and to know how the repairment and maintenance of the building on the hotel, and to review the condition of the existing damage of structural components, architecture, mechanical and electrical, exterior space and housekeeping categorized in heavy, medium and light damage. This study's methodology is qualitative and quantitative scripted research with observation methods, bibliography, qualitative, and documentation. The population and samples used are all Engineering Department employees because there are only fewer than 100 people. The results of the review of the data obtained are data on the Engineering Department's Organization Structure, Employee Job Description, and Workflow. In the implementation of repair and maintenance, 76% of employees already carried out, the largest massive damage review for the field of housekeeping is polishing granite marble 39.23 %. For the largest moderate damage is on the outer space field 30.85 %, then the largest minor damage is in the field of architecture of 58.71 %. These results serve as a guide in the planning of the annual work program.